التجربة الجزائرية في مجال ترقية الاستثمار في الطاقات المتجددة: دراسة تحليلية للبرنامج الوطني للطاقات المتجددة 2011-2030 - شعباني، لطفي علي; رحال، نصر; موفق، سهام (جامعة ابن خلدون تيارت - الملحقة الجامعية قصر الشلالة, 2019)
This study aims to shed light on the Algerian experience in the field of promotion of the investment in renewable energies through the analyzing of the national program of renewable energies 2011-2030. The researchers relied on the analytical descriptive method by analyzing the various projects included in the program according to the type of energy produced, as well as its impact on the national economy. At the end of the study, the researchers reached a series of results, the most prominent of which is that the national program for renewable energies embodies a serious development of the renewable energy industry in Algeria, In order to evaluate the results of the study, the researchers recommended the need to spread the culture of using renewable energies that proved economically feasible.
تهدف هذه الدراسة إلى تسليط الضوء على التجربة الجزائرية في مجال ترقية الاستثمار في الطاقات المتجددة، من خلال تحليل البرنامج الوطني للطاقات المتجددة 2011- 2030، وقد اعتمد الباحثين على المنهج الوصفي التحليلي، وذلك من خلال تحليل مختلف المشاريع التي تضمنها البرنامج حسب نوع الطاقة المنتجة، وكذا إيراز أثرها على الاقتصاد الوطني، ومع نهاية الدراسة توصل الباحثين إلى مجموعة من النتائج من أبرزها، أن البرنامج الوطني للطاقات المتجددة يجسد تطوير جدي لصناعة الطاقات المتجددة بالجزائر، ومن أجل تثمين نتائج الدراسة أوصى الباحثين بضرورة نشر ثقافة استخدام الطاقات المتجددة التي ثبتت جدواها اقتصاديا.
Keywords: الاقتصاد الجزائري -- البرامج التنموية -- الطاقات المتجددة -- الاستثمارات الطاقوية